GABAergic circuits control stimulus-instructed receptive field development in the optic tectum. - Richards, B; Voss, O; Akerman, C (2010)
During the development of sensory systems, receptive fields are modified by stimuli in the environment. This is thought to rely on learning algorithms that are sensitive to correlations in spike timing between cells, but the manner in which developing circuits selectively exploit correlations that are related to sensory inputs is unknown. We recorded from neurons in the developing optic tectum of Xenopus laevis and found that repeated presentation of moving visual stimuli induced receptive field changes that reflected the properties of the stimuli and that this form of learning was disrupted when GABAergic transmission was blocked. Consistent with a role for spike timing-dependent mechanisms, GABA blockade altered spike-timing patterns in the tectum and increased correlations between cells that would affect plasticity at intratectal synapses. This is a previously unknown role for GABAergic signals in development and highlights the importance of regulating the statistics of spiking activity for learning.